The Ethical Aspect of the Relationship of the Individual and the State in the Libertarian Perspective of Murray N. Rothbard - Płaszczyca, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2014)
On the grounds of the libertarian ethics presented by Murray N. Rothbard, thestate is an institution which acts against individuals and whole societies. The statesteals money from its citizens (taxes), stands in the way of free market developmentand controls the economy, thus hindering entrepreneurship. Besides that, thestate – through its rules and regulations – limits every man's right to make moralchoices. The state is an immoral institution, therefore its citizens have the right torefuse to pay taxes, follow orders, and even – in some circumstances – corruptcivil servants. In this paper we analyse Rothbard’s ethics and look into the argumentsof critics of libertarian thought. Practical social and economic solutions thatemerge from Rothbard’s point of view are also considered.